THE SYSTEM FE-PT-S AT 1100°C - Majzlan J.; Makovicky M.; Makovicky E.; Rose-Hansen J. (My University, 2002)
The system Fe–Pt–S at 1100°C contains four alloys, γ(Fe,Pt), PtFe, Pt3Fe and γ (Pt, Fe), with respective miscibility-gaps at 43.5–45.5 at.% Pt, 57.7–60.4 at.% Pt and 77–80 at.% Pt, two sulfide phases, Fe1− x S (maximum Pt solubility 1.1 at.% at 54.3 at.% S) and PtS (0.5–0.8 at.% Fe maximum), a Fe-rich sulfide melt (Pt solubility below microprobe limits) and a S-rich sulfide melt (Pt solubility 7.5 at.% for solidified melts with ~54.5 at.% S). Of the five two-phase and five three-phase associations, the most important are PtFe – Pt3Fe – Fe1− x S (Pt below detection), Pt3Fe – Fe1− x S (0.4 at.% Pt) – PtS, Pt3Fe – γ (Pt,Fe) – PtS and Fe1− x S (0.9 at.% Pt) – melt (~8.5 at.% Pt) – PtS. Comparisons of experimental data with natural associations enable us to suggest several genetic and geothermometric implications.
Keywords: system Fe–Pt–S; iron–platinum alloys; isoferroplatinum; monosulfide solid-solution; cooperite